Endocrine disruptors in teleosts: Evaluating environmental risks and biomarkers - Sonika Kar (Aquaculture and Fisheries, 2021)
Endocrine disruptors (EDs) are synthetic or natural chemical molecules occurring in environment that have the potential to impart adverse effects on homeostasis of endocrine axis leading to neurological, developmental, immunological and reproductive disarray at organismal level. A wide range of structurally diverse EDs such as, sex-steroid hormone mimics, pesticides and fertilizers, prevail in the environment originating from waste of industries, pharmaceutics, sewage treatment plants and agriculture. In addition, some metals, such as Cu, Hg and Zn, have endocrine disrupting potency in their metallic as well as synthesized nano-particulate forms. There is an increasing concern in research for the plausible threat posed by EDs that can disrupt the endocrine system in aquatic fauna as these compounds are frequently discharged or run-off into water stream. Fishes are well known bio-indicators to understand toxicity of EDs as they are vulnerable to endocrine disruption. Furthermore, EDs have the potential to affect fish-feeding higher vertebrates including mammals and subsequently human, as they make their way up on the food web pyramid due to biomagnification. In light of this, several observations suggesting adverse effects of EDs and the mechanism contributing to endocrine disruption in fish are discussed extensively in this review. This article highlights the necessity to choose a credible model for assessing the toxic effects exerted by EDs. Furthermore, the toxic effects of EDs will be comprehensively reviewed with reference to sexual plasticity, neuroendocrine mechanisms, thyroid and immune modulation, gonadal development and maturation as well as changes in transcriptome/genome profile using fish models to imply ED-induced aquatic pollution in a larger perspective. For decades now, studies on EDs have challenged traditional concepts in toxicology to develop new molecular markers to improve methodologies and to assess the ecological risks associated with field conditions. In this regard, it is imperative to highlight the development of modern diagnostic tools including biosensors to monitor the inadvertent usage of EDs and the resultant environmental risks. Lastly, current limitations in knowledge along with future research perspectives in the field are also highlighted in this article.